Forming of the new ethnic image of St.Petersburg - Anton Krasnov; Dmitriy Zhitin (European Regional Science Association (ERSA), 2015)
Ethnic and migration processes in Russia after the collapse of The Soviet Union have significantly changed the ethnic composition of major Russian cities. On the one hand, we see continuing of assimilation of most national communities which historically lived in the largest Russian cities (Ukrainians, Belarusians, Tatars, Jews etc.). On the other hand, the increased influx of migrants from the Republic of former Soviet Union led to the formation of new large ethnic communities. The paper deals with the transformation of the ethnic population structure of Russian cities on the example of St. Petersburg. Although St. Petersburg has five million inhabitants and national minorities accounts less than 8 percent in the population, this figure is increasing. In contrast to the situation 25 years ago, today we can see the areas where the concentration of different ethnic diasporas is significantly different from the mean value of the city. Thus, there are quite clearly distinguished areas where the prevalence of a particular ethnic group is significant. But on the contrary, there are areas where some ethnic groups almost completely absent. Since St. Petersburg is observed as a combination of more than hundred municipalities, all patterns can be seen quite clearly in a spatial aspect. And the phenomenon of spatial heterogeneity of resettlement of ethnic groups in St. Petersburg is the subject of the paper. The article contains materials of the censuses of the Soviet and Russian periods. Also we used cartographic techniques and methods of mathematical statistics to calculate the indicators needed to describe the degree of localization of the various ethnic groups. In addition, the correlation analysis of the resettlement of various ethnic groups has done.
Keywords: J15; 330; migrations; ethnic minorities; ethnic segregation; St.Petersburg